The Collaborative Remix of Cyberculture on the Web Project: Advancing Learning Through Students' Engagement - Junqueira, Eduardo S. (Proceedings of the International Conference on Networked Learning, 2012)
The paper presents the Collaborative Remix of Cyberculture on the Web Project's ongoing enactment at a Brazilian federal university. The project extends the activities of an on-campus course about Cyberculture as the instructor and current and former students engage in a collaborative process of co-designing a new web interface integrated by a remix of resources available on the internet and by students' own contributions. The Project's main objective is to advance students' learning about Cyberculture by engaging them with the interface co-design, the critical selection of resources and the production of their own materials. The instructor operates as a mediator, helping students develop a critical perspective about the Project and helping them make meaningful connections with the resources available on the internet. Former students act as brokers, aiding exchanges between the instructor and the students and supporting them in adding their imprint to the Project. The co-design of the web interface is detailed. Student response to this new way of participating and learning has been mixed. It is difficult for them to make sense of the new positioning of the instructor as a mediator instead of being the traditional solo holder of knowledge in class. But as the course evolves, students start to appreciate having the opportunity to share their ideas and to contribute to the Project, which leads to increasing participation and learning. Many students recognized that their involvement with the Project helped advance their learning as they had the opportunity to engage with new concepts and ideas related to the course and as they exchanged ideas and different points of view with their peers. Students also appreciated the production of original materials and the integration of these resources on the web interface. Challenges for the future are related to the need to bring new users to participate at the web interface, given that it is currently limited to the students, even though it is open on the internet. Also, new tools are necessary to help build meaningful connections between resources and to manage the continuous posting of new resources and the exchange of information on the web interface.